Competency Focused Versus Philosophically Grounded Health Promotion Practice: Impacts on Innovation and Addressing Health Inequities. (December 2022) - James, Tyler G.; Sullivan, Meagan K.; Henderson, Heather; Varnes, Julia R.
The professionalization of the fields of health education and health promotion has largely coincided with the completion of job task analysis conducted by major organizations in the field (e.g., the National Commission for Health Education Credentialing, Society for Public Health Education). The process through which these job task analyses and skill-based competencies are implemented in professional preparation programs poses a risk to stifle advancement and innovation in health education and promotion. In this perspective, we discuss Competency Focused Practice (the current state of the field) to a goal of Philosophically Grounded Practice. We provide comparisons of the implications of these two schools of thought with respect to ethics, social determinants of health, and practical methods in health education and promotion.